EVALUASI RESERVOAR FORMASI MENGGALA DAN PEMATANG PADA LAPANGAN âLANâ CEKUNGAN SUMATERA TENGAH - , LUTHFI ALFIAN NUGROHO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Final research on reservoir evaluation of Menggala and Pematang formation have been done on \"LAN\" field in the Central Sumatera Basin, in the working area of PT. Chevron Pacific Indonesia. This research aimed to determine the point of perforation from potential hydrocarbon reservoir on each well through calculation of shale volume, total porosity, effective porosity, permeability, and water saturation from both reservoirs. Then performed mapping distribution of shale volume, total porosity, effective porosity, and permeability in the area of research. Calculation of shale volume and porosity have been done with neutron-density method. Calculation of permeability have been done with applying equation from multiple regression method between NMR permeability log in well LAN-15 with shale volume and effective porosity to the whole wells. Calculation of water saturation have been done with Modified Simandoux equation. Research result show that the average value of shale volume for reservoir Menggala formation is 10,2% and reservoir Pematang formation is 15,9%, the average value of total porosity for reservoir Menggala formation is 20,6% and reservoir Pematang formation is 15,9%, the average value of effective porosity for reservoir Menggala formation is 19,5% and reservoir Pematang formation is 13,9%, the average value of permeability for reservoir Menggala formation is 442 mD and reservoir Pematang formation is 54 mD, the average value of effective water saturation for reservoir Menggala formation is 66,0% and reservoir Pematang formation is 86,7%. From the map of petrophysical properties distribution can be obtained some good quality zones, as north-western zone and south-eastern zone in reservoir Menggala formation, and western zone in reservoir Pematang formation. Perforation in the âLANâ field can be done in well LAN-1 (974â980 meter), LAN-2 (997â1.010 meter), LAN-3 (1.001â1.009 meter), LAN-4 (991â1.002 meter), LAN-5 (984â1.011 meter), LAN-9 (991â993 meter), LAN-15 (999â1.004 meter), LAN-16D (965â994 meter and 1.004â1.007 meter), LAN-19 (992â1.003 meter), and LAN-20 (982â995 meter).